Variability in storage potential of banana shoot cultures under medium term storage conditions - Houwe, Ines van den; Smet, K. de; Tezenas du Montcel, H.; Swennen, Rony L. (1995)
Shoot cultures of 401 banana clones were conserved under slow growth conditions (16±1°C, 25μmol m−2 s−1). Storage duration-defined as 60% survival time of 20 shoot cultures of a clone-averaged 334 days. However, large differences occurred among the different genomic (sub)groups and even within the same (sub)group. East-African highland bananas and non-plantain AAB bananas can be stored for significantly longer periods. Shoot tip cultures of another 41 banana clones conserved at higher ambient temperature (22±3°C) needed to be subcultured sooner (every 220 days on average).